The green braid : towards an architecture of ecology, economy, and equity - Tanzer, Kim; Longoria, Rafael; ebrary, Inc. (London : Routledge, Taylor & Francis Group, 2007)
This volume presents the discipline's best thinking on sustainability in written, drawn, and built form, drawing on over fifteen years of peer-reviewed essays and national design awards published by the Association of Collegiate Schools of Architecture (ACSA). Providing a primer on sustainability, useful to teachers and students alike, the selected essays address a broad range of issues. Combined with design projects that highlight issues holistically, they promote an understanding of the principles of sustainability and further the integration of sustainable methods into architectural projects. Using essays that alternately revise and clarify twentieth century architectural thinking, The Green Braid places sustainability at the centre of excellent architectural design. No other volume addresses sustainability within the context of architectural history, theory, pedagogy and design, making this book an ideal source for architects in framing their practices, and therefore their architectural production, in a sustainable manner.
The Green braid -- Meta-discourses in pedagogy and practice -- Phenomena and technology -- Building practices -- Settlement patterns -- The shared realm
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: architektura -- environmentální aspekty; ekodesign; ekologické stavby; udržitelný rozvoj; architecture -- environmental aspects; ecodesign; sustainable buildings; sustainable development; studie; sborníky; e-knihy online; studies; papers of several authors; e-books online